General Laws, Memorials and Resolutions of the Territory of Dakota 128, § 453 (4th Sess. 1864-65) - (:unkn) unknown (My University, 1864)
"Every person who manufactures or causes to be manufactured, or sells, or offers or keeps for sale, or gives or disposes of any instrument or weapon of the kind usually known as slung shot, or of any similar kind, is guilty of a misdemenor ."
Keywords: TRANSFER, MANUFACTURE & POSSESSION